Skema Aktan dan Model Fungsional Video Youtube “Pangeran Ikan” sebagai Bahan Ajar Menulis Cerita Fantasi Kelas VII SMP - Salma Dian Rhamadhan; Mukh Doyin (Universitas Muhammadiyah Magelang, 2026)
This research is motivated by the persistent obstacles in teaching fantasy story writing at the junior high school level, particularly in understanding narrative structure and developing a coherent storyline. Teaching fantasy story writing requires teaching materials that can help students understand the elements of story building concretely and systematically. This study aims to describe the narrative structure in the video